New oxford primary science level 5 (third edition) - Horsburgh, Nicholas (Oxford University Press; Karachi, 2022)
New Oxford Primary Science Level 4 introduces students to fundamental scientific concepts through engaging activities and experiments. The book encourages curiosity and critical thinking, helping young learners explore topics in biology, chemistry, physics, and environmental science.